SS18‐SSX‐regulated miR‐17 promotes tumor growth of synovial sarcoma by inhibiting p21WAF1/CIP1. Issue 9 (3rd September 2014) - Minami, Yusuke; Kohsaka, Shinji; Tsuda, Masumi; Yachi, Kazuhiro; Hatori, Nobuaki; Tanino, Mishie; Kimura, Taichi; Nishihara, Hiroshi; Minami, Akio; Iwasaki, Norimasa; Tanaka, Shinya
<x xml:space="preserve">Abstract</x> MicroRNA (miRNA) can function as tumor suppressors or oncogenes, and also as potential specific cancer biomarkers; however, there are few published studies on miRNA in synovial sarcomas, and their function remains unclear. We transfected the OncomiR miRNA Precursor Virus Library into synovial sarcoma Fuji cells followed by a colony formation assay to identify miRNAs to confer an aggressive tumorigenicity, and identified miR‐17‐5p from the large colonies. MiR‐17 was found to be induced by a chimeric oncoprotein SS18‐SSX specific for synovial sarcoma, and all examined cases of human synovial sarcoma expressed miR‐17, even at high levels in several cases. Overexpression of miR‐17 in synovial sarcoma cells, Fuji and HS‐SYII, increased colony forming ability in addition to cell growth, but not cell motility and invasion. Tumor volume formed in mice in vivo was significantly increased by miR‐17 overexpression with a marked increase of MIB‐1 index. According to PicTar and Miranda algorithms, which predicted CDKN1A (p21) as a putative target of miR‐17, a luciferase assay was performed and revealed that miR‐17 directly targets the 3′‐UTR of p21 mRNA. Indeed, p21 protein level was remarkably decreased by miR‐17 overexpression in a p53‐independent manner. It is noteworthy that miR‐17 succeeded in suppressing doxorubicin‐evoked higher expression of p21 and conferred the drug resistance. Meanwhile, introduction of anti‐miR‐17 in Fuji and HS‐SYII cells significantly decreased cell growth, consistent with rescued expression of p21. Taken together, miR‐17 promotes the tumor growth of synovial sarcomas by post‐transcriptional suppression of p21, which may be amenable to innovative therapeutic targeting in synovial sarcoma.